Hyperbaric hyperoxia in severe infections and sepsis: concepts and perspectives - Iazzetti, Paulo E.; Mantovani, Mário (Medicina (Ribeirao Preto), 1998)
We did a review, considering the relevant factors that could play a role in using hyperbaric oxygen therapy in sepsis. Specially in intra-abdominal infecctions due to gut Gram negative bacteria, stressing upon its interest to clinical and laboratory research. Some concepts related to hypoxia and oxidative metabolism are described, reviewing the role of oxygen free radical (reactive oxygen species or ROS) and anti-oxidants in sepsis development. The clinical use of HOT and in the clinical setting, and its potential in severe infections, are discussed.